Inovasi Kebijakan Program Kalimasada Melalui Jemput Bola Administrasi Kependudukan Di Kelurahan Wonorejo Rungkut - Ima Nur Rosyida; Yusuf Hariyoko (Eksekusi : Jurnal Ilmu Hukum dan Administrasi Negara, 2024)
E-Government and Digital Governance serve as crucial foundations in the transformation of public services, leveraging information and communication technology. The primary focus is to provide easy and efficient access for the community. Through innovations such as the "Jemput Bola Administrasi Kependudukan" (Administration Retrieval Initiative) within the Kalimasada program, the Surabaya city government expedites administrative processes by utilizing the Klampid New Generation (KNG) website. This research aims to optimize this innovation in the Wonorejo Rungkut sub-district of Surabaya. Standards of public service regulated by laws serve as benchmarks for enhancing service quality, covering procedures, processing time, costs, service offerings, infrastructure, and staff competencies. The research findings indicate that service procedures run smoothly, processing times are relatively fast, services are provided free of charge, service offerings include various citizenship documents, and infrastructure is adequate. This innovation reflects the integration of technology into governance, accelerating and streamlining public administration processes.